Dinamika Kelompok Tani Karet Di Desa Moris Jaya Kecamatan Banjar Agung Kabupaten Tulang Bawang - Zakaria Nawawi; Yuniar Aviati Syarief; Helvi Yanfika; Irwan Effendi (Fakultas Pertanian, Universitas Lampung, 2025)
Group dynamics can be achieved if a group can carry out all elements of group dynamics such as group goals, group structure, group task functions, group coaching, group atmosphere, and in terms of group pressure. A dynamic group will create an effective group. The location of the study was carried out in Moris Jaya Village, Banjar Agung District using a survey method with 42 respondents which was carried out in November - December 2024. The purpose of this study was to determine the dynamics of rubber farmer groups in Moris Jaya Village, Banjar Agung District, Tulang Bawang Regency and to determine the factors related to the dynamics of rubber farmer groups in Moris Jaya Village, Banjar Agung District, Tulang Bawang Regency. Descriptive statistical analysis and Spearman Rank correlation test were used to measure factors related to group dynamics and the relationship between group dynamics in increasing the effectiveness of rubber farmer groups. The results showed that leadership and member participation were included in the category related to group dynamics and group dynamics had a real relationship with the effectiveness of farmer groups. Group dynamics showed quite dynamic results.